Doom Spending Among Economics Education Students: A Psychological and Socioeconomic Perspective - supriadi, sudawan (Jurnal Pendidikan Ekonomi, 2025)
The development of digital technology and socio-economic changes have given rise to the phenomenon of doom spending, which is impulsive consumptive behavior in response to emotional stress, anxiety, or future uncertainty. This study aims to examine doom spending among students of the Economics Education Study Program from a psychological and socio-economic perspective. The approach used is qualitative with a case study design. Data was collected through indepth interviews and reflective questions to students who had engaged in doom spending behavior in the past three months. The results show that psychologically, college students tend to make impulsive spending to relieve emotional stress, which is accompanied by feelings of regret and awareness of a lack of self-control. From a socioeconomic perspective, doom spending behavior is related to limited financial literacy, lack of budget planning, and the influence of social media and the friendly environment. Although some students feel that their pocket money is sufficient, the tendency to engage in non-essential consumption remains high. This study concludes that doom spending is not only caused by individual factors, but is the result of a complex interaction between psychological conditions and socioeconomic backgrounds. Therefore, doom spending strategies need to involve a multidimensional approach, including financial education, emotional regulation training, and social interventions that support rational financial decision making.